Influential Article Review - Roadmap Application For Smart Electric Vehicles To Grid (V2g) - Moore, Leo; Gutierrez, Desiree (Journal of Strategic Innovation and Sustainability, 2019)
This paper examines technology. We present insights from a highly influential paper. Here are the highlights from this paper: Smart grid is defined as the overlaying of a unified communications and control system onto the existing power delivery infrastructure to provide the right information and the right entity at the right time. It helps even out demand spikes and uses resource mix more efficiently. It is a better integration, or “system balancing,” of variable resources, like wind power. Many of the advanced applications of smart grid are expected to develop in an evolutionary manner based on current technologies available and the needs of the market, for example, electric vehicles (EVs) or plug-in hybrid electric vehicles (PHEVs). It is likely that we will see a simpler associated application (i.e., smart battery charger) before the market matures to support a more complex form of the application vehicle-to-grid (V2G). The objective of this paper is to develop a technology road mapping (TRM) process for smart electric V2G technologies in Oregon and the Pacific Northwest (PNW). The research focuses on the application of V2G in the residential chargers. It introduces the market drivers, products, and technology analysis and provides research on the necessary resources needed within R&D in the coming years (next 10 years). For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.